United We Stand: Platforms, Tools and Innovation With the Unity Game Engine. (November 2019) - Foxman, Maxwell
The skirmish between game engines Unity and Unreal presents a new front in the platformization of cultural production. This article argues that such programs are "platform tools." They enable amateurs and professionals to not only build content for platforms but also "lock-in" industry ideologies in the ideation, production, implementation, and distribution of digital creative work, resulting in a homogeneity of developers, practices, and products. The Unity engine's history, features, and place in the game production pipeline makes it a paradigmatic "platform tool." Findings from 90 interviews with VR enthusiasts show that Unity set the boundaries or "rules" for developers' everyday activities and, despite enthusiasm about the medium's potential, compelled them to create content which conformed to popular gaming genres and standards.